1998
DOI: 10.1182/blood.v92.2.596.414k05_596_599
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability and Specificity of c-kit for the Diagnosis of Acute Myeloid Leukemias and Undifferentiated Leukemias

Abstract: We document findings on c-kit (CD117) expression in 1,937 pediatric and adult de novo acute leukemia cases, diagnosed in five single European centers. All cases were well characterized as to the morphologic, cytochemical, and immunologic features, according to the European Group for the Immunological Classification of Leukemias (EGIL). The cases included 1,103 acute myeloid leukemia (AML), 819 acute lymphoblastic leukemia (ALL), 11 biphenotypic acute leukemia (BAL), and 4 undifferentiated (AUL). c-kit was expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0
8

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 8 publications
5
59
0
8
Order By: Relevance
“…These mixed-lineage leukaemias probably included both true BAL and other forms of AL with aberrant expression of one or two markers of another lineage. The BAL scoring system forwarded by EGIL (Bene et al, 1995;Bene et al, 1998) is based on the number and specificity of the myeloid and lymphoid antigens expressed simultaneously on leukaemic cells. Although several antigens are considered lineage-specific (such as CD3 and TCR on T-lymphoid cells, and MPO on myeloid cells), other markers are not restricted to a specific lineage; for example, CD2 and CD7 have been found on myeloid blasts (Buccheri et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…These mixed-lineage leukaemias probably included both true BAL and other forms of AL with aberrant expression of one or two markers of another lineage. The BAL scoring system forwarded by EGIL (Bene et al, 1995;Bene et al, 1998) is based on the number and specificity of the myeloid and lymphoid antigens expressed simultaneously on leukaemic cells. Although several antigens are considered lineage-specific (such as CD3 and TCR on T-lymphoid cells, and MPO on myeloid cells), other markers are not restricted to a specific lineage; for example, CD2 and CD7 have been found on myeloid blasts (Buccheri et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…CD117, the receptor for stem cell factor, is expressed on immature normal and leukaemic myeloid cell but only rarely on leukaemic blasts in B-cell precursor ALL (Bene et al, 1998;Sperling et al, 1997). Thus, CD117 was thought a be another good candidate to separate normal from leukaemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…In all six patients (UPN 1,7,9,18,20 and 26) an AC133-positive CD19 À CD34 progenitor/stem cell population could be detected, whereas the CD19 CD34 /leukaemic cell clone was AC133-negative (Fig 2). Expression of CD117 within the CD19 À CD34 cell compartment Due to the rarity of CD117 expression in B-cell precursor ALL (Bene et al, 1998;Sperling et al, 1997), CD117 was thought to be a good marker to distinguish between residual normal and leukaemic cells. Analysis of CD117 expression on CD45negative B-cell precursor ALL has shown that the CD19 À CD34 CD45 candidate normal progenitor/stem cells expressed CD117 (patient UPN 11, Fig 1; UPN 12, Fig 3; UPN 25; UPN 28).…”
Section: Expression Of Ac133 and Cd117 Within The Leukaemic Cell Clonementioning
confidence: 99%
“…Specific receptors are absolute requirements for cytokine action to occur. However, many growth factor receptors are manifested in a low density both on normal and leukemic progenitors and receptor expression may not be detected in a resting metabolic or proliferative state [58][59][60][61][62][63]. If only a small fraction of blast cells are clonogenic and the number of specific cytokine binding sites is low, most assays may not be sensitive enough to detect receptor expression at the protein level, unless a significant portion of non-clonogenic cells express the same receptor [64,65].…”
Section: Assessing the Response Of Leukemic Cells To Cytokinesmentioning
confidence: 99%